6x+7=8x-16

Simple and best practice solution for 6x+7=8x-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7=8x-16 equation:


Simplifying
6x + 7 = 8x + -16

Reorder the terms:
7 + 6x = 8x + -16

Reorder the terms:
7 + 6x = -16 + 8x

Solving
7 + 6x = -16 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
7 + 6x + -8x = -16 + 8x + -8x

Combine like terms: 6x + -8x = -2x
7 + -2x = -16 + 8x + -8x

Combine like terms: 8x + -8x = 0
7 + -2x = -16 + 0
7 + -2x = -16

Add '-7' to each side of the equation.
7 + -7 + -2x = -16 + -7

Combine like terms: 7 + -7 = 0
0 + -2x = -16 + -7
-2x = -16 + -7

Combine like terms: -16 + -7 = -23
-2x = -23

Divide each side by '-2'.
x = 11.5

Simplifying
x = 11.5

See similar equations:

| -017+(-3.546)= | | -3(-7y+7)-5y=4(y-7)-7 | | 152+13x+8+10x+6=180 | | 5n+23=38 | | 8600.00=8000.00(1+rt) | | -7w+9=-5(w-5) | | 2q+1=q+g | | 3(5n+5)-6=2(3n-6) | | 2y^2-2y=0 | | i=z^8 | | 9(v+7)=-3v+27 | | 10=3+c | | (z^8)-i=0 | | 9x+6-12x=-7+2x-12+5x | | 2r(r+3)=0 | | 7(w-4)+8w=2 | | 3x+3y-3x+4y= | | 2/5x-1/3=2/15 | | 4a^3-44a^2=0 | | -6u+3(u+4)=-18 | | 8y=7y+1 | | x^2+x+6=4x+4 | | 4r^2+28r=0 | | 2/3•3=6/3 | | 2/3-1/6x=5/12 | | 11b+7=4 | | 4/3=n-4/n | | 49=6x+x | | 3n-3=-8(5+5n) | | 5-3a=2 | | 45=4x^2+x^2 | | 50=x+22 |

Equations solver categories